SEANERN member snapshots: an overview of nursing practice and education in ASEAN and Asia - Nurumal, Mohd. Said; Nik Ismail, Nik Safiah (Faculty of Nursing, Chiang Mai University, 2019)
An overview of nursing practice and education in ASEAN and Asia